2009
DOI: 10.1111/j.1471-4159.2009.05982.x
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic and extrasynaptic GABA transporters as targets for anti‐epileptic drugs

Abstract: Epilepsy is a heterogeneous disorder that is characterized by the presence of both convulsive and non-convulsive seizures. Moreover, epilepsy is one of the most prevalent neurological disorders that does not discriminate according to age, gender, race, or socioeconomic status. Worldwide, there are over 50 million people afflicted by this disorder and approximately 50% of patients with epilepsy can be effectively treated with the currently available anti-epileptic drugs. For another 20%, their seizures are inad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 26 publications
(41 reference statements)
3
78
0
Order By: Relevance
“…Seizure severity was graded according to a modified Racine scale. 4,14 Fifteen minutes after kainate injection, the mice were injected intraperitoneally with a combination of [1-13 C]glucose (543 mg/kg) and [1,[2][3][4][5][6][7][8][9][10][11][12][13] C]acetate (504 mg/kg) and after another 15 minutes, the brains of the mice were subjected to microwave fixation at 4 kW for 1.7 seconds (model GA5013, Gerling Applied Engineering, Modesto, CA, USA). This is the most humane euthanization method instantly inactivating proteins in the brain.…”
Section: Metabolic Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Seizure severity was graded according to a modified Racine scale. 4,14 Fifteen minutes after kainate injection, the mice were injected intraperitoneally with a combination of [1-13 C]glucose (543 mg/kg) and [1,[2][3][4][5][6][7][8][9][10][11][12][13] C]acetate (504 mg/kg) and after another 15 minutes, the brains of the mice were subjected to microwave fixation at 4 kW for 1.7 seconds (model GA5013, Gerling Applied Engineering, Modesto, CA, USA). This is the most humane euthanization method instantly inactivating proteins in the brain.…”
Section: Metabolic Studiesmentioning
confidence: 99%
“…If [4,[5][6][7][8][9][10][11][12][13] C]a-ketoglutarate remains in the astrocytic TCA cycle for further metabolism via this pathway, it will, after condensation with unlabeled acetyl CoA, give rise to [3-13 C]-and [1,2-13 C]a-ketoglutarate in the subsequent turn, which may give rise to glutamate and glutamine displaying the same labeling patterns. Based on the distinct 13 C labeling in glutamine after the first and second turn of TCA cycle metabolism, a number indicative of astrocytic TCA cycle activity can be calculated by relating the amount of isotopomers generated in the second turn of TCA cycle metabolism to the amount of that generated in the first turn, i.e., ( [1,[2][3][4][5][6][7][8][9][10][11][12][13] …”
Section: Nuclear Magnetic Resonance Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Proof of concept that GAT inhibitors mediate anticonvulsant activity in rodents has been firmly established (Nielsen et al, 1991;White et al, 1993White et al, , 2002White et al, , 2005Madsen et al, 2009Madsen et al, , 2010. Furthermore, it has been demonstrated that an inhibitor of BGT1 having no affinity for GABA i.e., 4,5,6,7-tetrahydrobenzo[d]isoxazol-3-ol (EF1502) when administered in combination with inhibitors of GAT1 (i.e., tiagabine) and N- [4,5,6,, results in a synergistic anticonvulsant effect in audiogenic seizure (AGS)-susceptible Frings mice (White et al, 2005).…”
Section: Introductionmentioning
confidence: 99%